Distance, Equity and Older People’s Experiences in the Nordic Periphery - Begum, Shahnaj; Harbison, Joan R.; Naskali, Päivi; Zechner, Minna (Taylor & Francis, 2024)
This book demonstrates how the largely neglected and multifaceted concept of distance can be used as a primary lens to expand and enrich our understandings of what older people say about their lives, needs and wishes in diverse surroundings in the Northern periphery and beyond. It asks how physical, social and emotional distances shape older people’s everyday lives and practices. Contributions from leading experts provides interdisciplinary investigations into the experiences and stories of older people in the Northern periphery. These insights demonstrate the utility of the concept, distance, when reflecting on the central aspects of contemporary ageing societies. The book explores key themes such as care, age politics, technology, intergenerational relations and migration, providing perspectives that are applicable across a variety of international geographical contexts. This innovative book offers a valuable theoretical and methodological contribution with critical new perspectives on ageing in relation to distances. It will be of interest to students and scholars interested in sociology, human geography, health and social care, ageing and gerontological studies, gender studies and Arctic studies.